Concentrations and abundance ratios of long-chain alkenones and glycerol dialkyl glycerol tetraethers in sinking particles south of Java. (June 2016) - Chen, Wenwen; Mohtadi, Mahyar; Schefuß, Enno; Mollenhauer, Gesine
Abstract: In this study, we obtained concentrations and abundance ratios of long-chain alkenones and glycerol dialkyl glycerol tetraethers (GDGTs) in a one-year time-series of sinking particles collected with a sediment trap moored from December 2001 to November 2002 at 2200 m water depth south of Java in the eastern Indian Ocean. We investigate the seasonality of alkenone and GDGT fluxes as well as the potential habitat depth of the Thaumarchaeota producing the GDGTs entrained in sinking particles. The alkenone flux shows a pronounced seasonality and ranges from 1 µg m −2 d −1 to 35 µg m −2 d −1 . The highest alkenone flux is observed in late September during the Southeast monsoon, coincident with high total organic carbon fluxes as well as high net primary productivity. Flux-weighted mean temperature for the high flux period using the alkenone-based sea-surface temperature (SST) index U 37 K ′ is 26.7 °C, which is similar to satellite-derived Southeast (SE) monsoon SST (26.4 °C). The GDGT flux displays a weaker seasonality than that of the alkenones. It is elevated during the SE monsoon period compared to the Northwest (NW) monsoon and intermonsoon periods (approximately 2.5 times), which is probably related to seasonal variation of the abundance of Thaumarchaeota, or to enhanced export of GDGTs by aggregation with sinking phytoplankton detritus. Flux-weighted mean temperature inferred from the GDGT-based TEX 86 H index is 26.2 °C, which is 1.8 °C lower than mean annual (ma) SST but similar to SE monsoon SST. As the time series of TEX 86 H temperature estimates, however, does not record a strong seasonal amplitude, we infer that TEX 86 H reflects ma upper thermocline temperature at approximately 50 m water depth. Highlights: Eastern Indian Ocean Record of alkenones/ U 37 K ′ and GDGTs/TEX86 in sinking particles. Alkenone fluxes are strongly seasonal and occur mainly during upwelling. U 37 K ′ temperature estimates correspond to SST during the onset and end of upwelling. GDGT fluxes have weaker seasonality than alkenone fluxes. TEX86 appears to reflect temperatures at approximately 50 m water depth.